Impact of Early pregnancy bleeding on maternal and fetal outcome - S. ELghazala, Zahia; H. Elhararya, Fawzia; I. Altaybb, Alla; A. Alshekteriac, Amina (Libyan Journal of Science &Technology, 2024)
Background: Vaginal bleeding is a common event at all stages of pregnancy, and early pregnancy bleeding during the first and second trimester (EPB) is a common symptom during pregnancy. EPB could have adverse effects on pregnancy and neonate. Objective: Is to assess the effects of early pregnancy bleeding on both mother and fetus. Patients and methods: A descriptive, cross-sectional study was conducted at Benghazi medical center (BMC); all the eligible women attended the obstetric ward for delivery in the period between the 1st of August and 31th of December 2016 were included. Data collected by direct interview and from medical records. Data analyzed using SPSS ver. 23. Descriptive statistics were obtained, and means, standard deviation, and frequency distribution were calculated. Chi square test was used, P< 0.05 considered as statistically significant. Results: Out of the 1404 women, 125 (9%) women had a history of early pregnancy bleeding (EPB). Pregnancy-induced hypertension, pre-eclamptic toxemia, antepartum hemorrhage, preterm labor, and premature rupture of the membrane were significantly (P<0.05) more frequent among women with a history of early bleeding. Ninety-four (3.5%) women had a history of antepartum hemorrhage, for 27 (1.9%) of them, the cause was due to placenta abruption, while for 22 (1.6%) women the cause was placenta previa. The occurrence of both placenta previa and placenta abruption was significantly (P<0.05) more among women with a history of EPB. Fetal health problems and early neonatal death were significantly (P<0.05) more among mothers with EPB. Conclusion: Serious maternal morbidities are significantly associated with EPB as PET, APH, and PROM. Also prematurity, IUGR, low birth weight, increase risk of neonatal ward admission and perinatal mortality are significantly more among women EPB. Recommendation: Proper antenatal care for early diagnosis, close follow up, and proper management of women with early pregnancy bleeding strongly recommended.